2020
DOI: 10.1002/hbm.25314
|View full text |Cite
|
Sign up to set email alerts
|

Extended‐amygdala intrinsic functional connectivity networks: A population study

Abstract: Pre‐clinical and human neuroimaging research implicates the extended‐amygdala (ExtA) (including the bed nucleus of the stria terminalis [BST] and central nucleus of the amygdala [CeA]) in networks mediating negative emotional states associated with stress and substance‐use behaviours. The extent to which individual ExtA structures form a functionally integrated unit is controversial. We utilised a large sample (n > 1,000 healthy young adult humans) to compare the intrinsic functional connectivity networks (ICN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 151 publications
(333 reference statements)
0
5
0
Order By: Relevance
“…Whilst not specific to the BNST, white matter abnormalities of the fornix in adults with heavy drinking and alcohol use disorder have been reported ( Cardenas et al., 2013 ), although the diffusion MRI literature in general with regards to correlates of substance abuse is somewhat inconsistent ( Benear et al., 2020 ). Similar to our dispositional negativity component, a reason we did not find such an association could be that our sample consisted of a screened, relatively healthy population (median drinks consumed per week being two), which likely reduced our chances of finding any association ( Berry et al., 2020 ). Studies that have found associations between alcohol use and white matter metrics have generally been conducted either with clinical populations, or following experimental manipulations ( Campbell et al., 2019 ; Cardenas et al., 2013 ; Flook et al., 2021 ).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Whilst not specific to the BNST, white matter abnormalities of the fornix in adults with heavy drinking and alcohol use disorder have been reported ( Cardenas et al., 2013 ), although the diffusion MRI literature in general with regards to correlates of substance abuse is somewhat inconsistent ( Benear et al., 2020 ). Similar to our dispositional negativity component, a reason we did not find such an association could be that our sample consisted of a screened, relatively healthy population (median drinks consumed per week being two), which likely reduced our chances of finding any association ( Berry et al., 2020 ). Studies that have found associations between alcohol use and white matter metrics have generally been conducted either with clinical populations, or following experimental manipulations ( Campbell et al., 2019 ; Cardenas et al., 2013 ; Flook et al., 2021 ).…”
Section: Discussionmentioning
confidence: 68%
“…The BNST mask was downloaded from the NeuroVault website ( https://neurovault.org/collections/3245 ), originally uploaded by Theiss et al ( Mai et al., 2015 ; Theiss et al., 2017 ; Tillman et al., 2018 ). This mask was thresholded to a minimum probability of 25%, in accordance with previous studies ( Berry et al., 2020 ; Theiss et al., 2017 ). The thalamic nuclei mask centred on the anteroventral ROI taken from the Automated Anatomical Labelling Atlas 3 ( Rolls et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we repeated the dMRI tractography analysis in a large human sample, the Young Adults Human Connectome Project (HCP) (n = 1206). As well as containing high quality neuroimaging data (Sotiropoulos et al, 2013;Van Essen et al, 2012), this sample has been richly phenotyped; allowing for the examination of relationships between dMRI white matter microstructure and stress-related traits (reflecting dispositional negativity and alcohol use, derived in a previous study (Berry et al, 2020). Finally, we used the family structure of the HCP to assess the heritability, and co-heritability, of our dMRI microstructure measures and derived stress-related traits.…”
Section: Study Aimsmentioning
confidence: 99%